APRESENTAÇÃO - MOREIRA, Glauber Lima; AZEVEDO, Diego Napoleão Viana; CARVALHO, Adriana da Rocha; SILVA JÚNIOR, Antonio Ferreira da (Caminhos em Linguística Aplicada, 2025)
APRESENTAÇÃO - VOL 31, Nº1, 2025